Inhibition of Hemolysis of Red Blood Cells by Citrullus colocynthis, Ilex spinigera and Gleditsia caspica Extracts - M Mohadjerani; M Damanjany (Institue of Medicinal Plants, ACECR, 2015)
Background: Many plants chemical substances that possess antioxidant properties, were known that might have an antihemolytic effect on erythrocytes. The use of synthetic antioxidants however, has been limited because of their toxicity and side effects. Therefore, medical researchers have intensified their quest to find natural antioxidants. Objective: The effect of extract of leaf and pulp of Citrullus colocynthis, leaf of Ilex spinigera and leaf and fruit of Gleditsia caspica as medicinal plants were investigated on red blood cell hemolysis. Methods: The plants were extracted in MeOH as solvent by soxhlet apparatus. Blood samples were collected from health volunteers and divided into two groups: test and control. Red blood cell peroxidation for each extract (5 - 150 µg/ml) was induced using AAPH (2, 2´-azo-bis-(2-amidinopropane) dihydrochloride) (35 mM). Percentage of hemolysis was measured spectrophotometrically by reading the absorbance at 540 nm as released hemoglobin from the cell in the presence and absence of the extracts. Results: Leaf extract of Gleditsia caspica with IC50: 5.58 ± 0.03 µg/ml and Ilex spinigera with IC50: 13.85 ± 0.02 µg/ml showed the higher inhibitory effect on hemolysis among other extracts. Conclusion: The results show that the use of the plants, Gleditsia caspica and Ilex spinigera, as natural antioxidants in the prevention and treatment of many diseases, including hemolysis of red blood cells by oxidizing agents can be studied.